From Teaching to Thriving: Exploring the Lived Experiences of English Education Graduates in Non-Teaching Careers - Nabilah, Jihan; Teodora Ping, Maria; Hermagustiana, Istanti; Sunardi; Sunggingwati, Dyah; Rusmawaty, Desy (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
The present phenomenological study discovers the lived experiences of English education graduates pursuing non-teaching careers (any professional roles that do not involve teaching students in formal educational settings). By conducting in-depth interviews with three participants, their lived experiences uncovered the interaction between non-teaching career exploration, appealing job opportunities, interest-driven career decisions, career choice consistency, self-efficacy, confidence, career growth, and development opportunities, which guided them to pursue their non-teaching careers. They considered intrinsic factors (self-efficacy and confidence, personal goals, personal interest, personal development, and outcomes expectations), along with extrinsic factors (financial stability, teaching limitations, career prospect, workload vs. compensation, continued engagement with educational background) in deciding their careers. The skills from English education such as teaching, communication, critical thinking, problem-solving, and English skills are applicable to help them adapt to their non-teaching career. The findings prove the adaptability of English education graduates in managing job market difficulties and diverse applications of their educational experiences. By having these facts this study informs higher education institutions and English education programs to support and guide the English education graduates as they fit for diverse career paths.